2020
DOI: 10.1101/2020.03.19.999268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 Vpr-induced Proinflammatory Response and Apoptosis are Mediated through the Sur1-Trpm4 Channel in Astrocytes

Abstract: There are about 38 million people currently living with HIV/AIDS worldwide. Successful treatment with combinational antiretroviral therapies (cART) can eliminate active replicating viruses and prolong lives to nearly normal lifespans. However, the new challenge faced by more than half of those HIV-infected and aging patients is chronic CNS neuroinflammation, which leads to HIVassociated neurocognitive disorders (HAND). While severe and progressive HAND has decreased significantly due to cART, chronic HAND ofte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Inhibition of NF-κB activity can reverse neuronal autophagy induced by Tat [90]. We recently reported that HIV-1 Vpr-induced proin ammatory response and apoptotic cell death are mediated through the NF-kB activation in astrocytes [91]. Targeting NFkB may ameliorate HIV-associated neuroin ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-κB activity can reverse neuronal autophagy induced by Tat [90]. We recently reported that HIV-1 Vpr-induced proin ammatory response and apoptotic cell death are mediated through the NF-kB activation in astrocytes [91]. Targeting NFkB may ameliorate HIV-associated neuroin ammation.…”
Section: Discussionmentioning
confidence: 99%